Beliefs and perceived barriers in purchasing cosmetic surgery services: The consumer decision-making process and the reasoned action approach - Rawlins, Pia (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The cosmetic surgery industry has seen a substantial increase in demand in recent years. It is clear, that professional services, such as health care, elicit unique consumer behaviour and decision-making strategies. Past research has shown that factors such as body-image dissatisfaction, aging anxiety and appearance investment, among others, explain interest and likelihood of pursuing cosmetic surgery. Additionally, past research has identified characteristics that influence consumers’ selection of a health care service provider. However, these types of investigations, while closely involved with the phenomenon of interest, do not tell us anything about the reasons why a potential consumer in the target segment would not want to purchase cosmetic surgery services in general. This is a glaring research-gap. Thus, the purpose of this thesis is to uncover how and why consumers make decisions about utilizing cosmetic surgery services. On a managerial level, the research aims to identify reasons why potential target consumers do not wish to utilize cosmetic surgery. The following research questions are proposed: RQ1: What is the nature of the consumer decision-making process when purchasing cosmetic surgery services? RQ2: What beliefs do consumers associate with utilizing cosmetic surgery services? RQ3: How do these beliefs translate into possible barriers for purchase? The reasoned action approach states that the key to understanding any behaviour lies in the behavioural, normative and control beliefs related to that specific behaviour. A qualitative approach to the research problem was chosen. A group of four potential consumers of cosmetic surgery, four existing consumers of cosmetic surgery and two industry professionals, were interviewed using semi-structured interviews and an elicitation process in order to uncover the nature of the decision-making process, identify beliefs related to utilizing cosmetic surgery and resolve how they translate into perceived barriers to action. Results suggest that when purchasing cosmetic surgery, consumers’ decision-making processes may differ among individuals. Some support as well as slight opposition was found for previous research on the topic, further implying that decision-making processes can vary between individual professional services. The research uncovered 7 behavioural beliefs, 7 normative beliefs and 3 control beliefs influencing behaviour. Lack of money and time were most clearly identified as direct barriers to action, but additionally fear or pain or harm, service failure, addiction and social rejection were identified as indirect barriers. Respondents indicated fairly strong underlying fears of social judgement, which discontents trends indicating the softening of general attitudes towards the industry.